The Efforts to Improve Basic Writing Skills of 4-5 Year Old Children Through Rubber Seed Collage at TK Islam Al-Husein - Uyun, Fahrotul; Zahro, Ianatuz; Siswono, Hendrik (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
This study aims to improve the basic writing skills of children aged 4-5 years through collage activities using rubber seeds at TK Islam Al-Husein. The research employs the Classroom Action Research (CAR) method using the Kemmis & McTaggart model, implemented in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects were 12 children from Group A, with data collection techniques involving observation, documentation, and informal interviews.The results show a significant increase from the pre-cycle to cycle II. In the pre-cycle, no children (0%) achieved the minimal "Developing as Expected (BSH)" category. After Cycle I, the achievement rose to 33.33% of children in the BSH category. In Cycle II, 75.00% had reached the minimal category, with details as follows: Developing Well (BDB) at 33.33% (4 children), Developing as Expected (BSH) at 41.67% (5 children), and Starting to Develop (MB) at 25.00% (3 children). This improvement reflects the effectiveness of the rubber seed collage activity in training hand-eye coordination, strengthening fine motor skills, and fostering children's motivation to learn to write. Thus, the collage method using rubber seeds can be recommended as a creative learning medium to stimulate pre-writing skills in early childhood.